Profile of Student’s Critical Thinking Skills and The Effectiveness of Problem-Based Learning Models Assisted by Digital Worksheet in Science Learning on Motion and Force Materials - Risa Umami; Madlazim Madlazim; Sifak Indana (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: Critical thinking skills are one of the 21st-century skills that must be possessed by students in order to be able to adapt and compete on a global scale. This study aims to describe the profile of students' critical thinking skills and the effectiveness of the Problem-Based Learning (PBL) models assisted by digital worksheets to improve students' critical thinking skills In Learning Science On Motion And Force Materials. Method: The research design is quantitative descriptive research. The subjects of this study were 102 students at SMPN 4 Waru with a simple random sampling method. Critical thinking skills tests are analyzed per indicator, which consists of giving simple explanations, building basic skills, concluding, giving advanced explanations, and setting strategies and tactics. Results: Based on the results of the analysis, it was obtained that the average proportion of students' thinking skills was in the low category. The indicator that gets the highest percentage is giving a simple explanation at the lowest indicator is setting strategy and tactics. Several factors cause this: learning rarely leads students to train and improve their critical thinking skills, the evaluation instruments used primarily using low cognitive tests, and the learning loss factor students experience while studying at home due to the effects of the COVID-19 pandemic. Novelty: Based on several research sources, it was concluded that applying the PBL model assisted by digital worksheets could effectively improve students' critical thinking skills in science learning.